Women’s knowledge on activities associated with maternal hyperthermia during pregnancy. A cross-sectional study of the sample of Polish women - Szatko, Alicja; Boryszewska, Martyna; Mabiala, Ewelina; Kacperczyk-Bartnik, Joanna; Dobrowolska-Redo, Agnieszka; Zaręba-Szczudlik, Julia; Romejko-Wolniewicz, Ewa (Polish Journal of Public Health, 2018)
Introduction. Hyperthermia during the first trimester increases the risk of miscarriage and birth defects. A variety of activities predisposing to hyperthermia during pregnancy such as attending sauna, hot tubs or solarium may lead to irreversible abnormalities of the developing fetus.Aim. The aim of the study was to assess women‘s knowledge on the risks of maternal hyperthermia during each trimester of pregnancy.Material and methods. It was a cross-sectional study conducted by means of an anonymous questionnaire. The study group included 302 women aged 17-65 who were admitted to a tertiary referral hospital. The questionnaire was designed on the basis of the Committee Opinion formulated by the American College of Obstetricians and Gynecologists and was consisted of two sections: demographic data and respondents‘ opinions on activities associated with hyperthermia in pregnancy. Statistical analysis was conducted to estimate the association of age, level of education and obstetrical status.Results. The lowest percentage of given proper answers was observed in case of questions about early pregnancy. There was no association between respondents‘ level of education and choice of correct answers. Current pregnancy was associated with higher awareness of contraindicated using of hot tubs and steam rooms.Conclusions. Patients‘ education concerning hyperthermia in pregnancy should focus on information about high risk of birth defects caused by overheating in the early pregnancy and a variety of activities linked with temperature elevation.